1995
DOI: 10.1177/43.1.7822766
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of rK9, an enzyme of the kallikrein gene family, in the rat ventral prostate.

Abstract: The rat kallikrein family consists of multiple closely related proteins. Most of these proteins have been purified from rat submandibular gland (SMG), among them rK9, an enzyme that has a direct vasoconstrictory effect on isolated aortic rings. Recently, two members of the kallikrein family, rK8 and rK9, were also purified from rat prostate, whereas other family members were not detected in this organ. In the present study, the immunohistochemical localization of rK9 was determined in rat prostate by the indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Comparison of the amino acid sequences of p18 and the known sequences in the protein database demonstrated that the first 18-amino-acid sequence of p18 and the sequence of rat glandular kallikrein 9 (rKLK9) were identical (100% identity). Rat glandular kallikrein 9 (rKLK9) is one of the proteins encoded by a group of genes showing a high degree (74-86%) of sequence similarity, which is known as the kallikrein gene family, since one of the genes encodes tissue kallikrein (rK1) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the amino acid sequences of p18 and the known sequences in the protein database demonstrated that the first 18-amino-acid sequence of p18 and the sequence of rat glandular kallikrein 9 (rKLK9) were identical (100% identity). Rat glandular kallikrein 9 (rKLK9) is one of the proteins encoded by a group of genes showing a high degree (74-86%) of sequence similarity, which is known as the kallikrein gene family, since one of the genes encodes tissue kallikrein (rK1) [21].…”
Section: Discussionmentioning
confidence: 99%